The use of virtual reality as an innovation in medical e-education : a perception study / Fieza Hasnora Hashim Bakhtiar - Hashim Bakhtiar, Fieza Hasnora (Faculty of Computer and Mathematical Sciences, 2005)
The internet has change the way of doing business, learning and all activities in daily life. The extent of organizational innovation with information technology, an important construct in the innovation literature, has been measured in many different ways. Some measures have a narrow focus while others aggregate innovative behaviors across a set of innovations or stages in the assimilation lifecycle. There has been a lot of research has been done in the foreign country such as Canada about the virtual reality and they are had implement it. Virtual reality is the development of artificial environments that can be navigated directly. It is a computer generated environment with and within which people can interact. The advantage of VR is that it can immerse people in an environment that would be unavailable. As in the learning environment, the students are immersed in the virtual reality learning environment and there are no distractions to learning. This research will discover on what is the perceptions of the respondents' on using virtual reality as innovations in medical e-education. The outcome will be usefiil to see the potential usage of it.